Forage Plants of Gaur (Bos gaurus H. Smith, 1827) in Tropical Forest of Southern India - Ashokkumar, M.; Swaminathan, S.; Desai, Ajay A.; Nagarajan, R. (Indian Forester, 2021)
Forage plant species of Gaur (Bos gaurus) were studied by direct observation using focal sampling (90 hours) about 30 hours of sampling in three major habitats (Tropical dry deciduous forest, Moist deciduous forest and Thorn forest) in Mudumalai Tiger Reserve, Southern India from Jan-2003 to Aug-2004, also studied by feeding trail plots (924 1m2 plots and 495 5m2 plots) sampled in all the habitats. Gaur was observed to forage on 155 species of plants belonging to 38 families under 23 orders. Among different plant, physiognomic types trees and shrubs constituted a greater proportion by orders Rosales and Malvales. Herbs constituted 32% of the overall plant selected and consisted of 49 species in 17 orders and dominated by Asterales. The plant families such as Poaceae, Fabaceae, Asteraceae and Malvaceae collectively formed the major food species. Among the different species 29 grass, 9 herb species, 9 shrubs and 11 tree species were having more than one preference value. Gaur prefers to forage on Cenchrus purpureus, Axonopus compressus, Sprobolus diander, Themeda triandra, Oplismenus undulatifolius among grasses and Asystasia chelonoides and Sida cordifolia among herbs. The forage plant species of gaur was compared and discussed with other habitats of gaur distributional range.